2019
DOI: 10.32598/jccnc.5.1.25
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Medical-Directed Play on the Severity of Pediatric Pain During Burn Dressing Change in Children: A Clinical Randomized Trial

Abstract: Background: Pain management of children with burn is one of the most important issues in pediatric medicine. Non-pharmacological methods of pain control can play an important role in suitable patients. This study was conducted with the aim of investigating the effect of Medical directed play on the severity of pediatric pain during burn dressing change. Methods: A randomized controlled trial was conducted on 82, 3-to 6-year-old children referring to a burn center in Tehran, Iran, for their first burn dressing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…The findings in the same line with Donnelly (2016) he was found that, there were significant differences between pain intensity before and after videogames distraction, where total pain level means decreased following video game distraction technique. Also, Moosavi et al, (2019) supported this finding and found that there were significant reductions in pain for those wearing the head-mounted displays and also for those playing by the mobile device. Meanwhile, Hassannia et al, (2021) supported this finding in a similar study entitled and found that the virtual reality as a distraction technique significantly reduced pain at the onset of circumcision, during anesthesia and at the end of the circumcision.…”
Section: Effect Of Video Games On Postoperative Pain Among Preschool ...mentioning
confidence: 53%
See 1 more Smart Citation
“…The findings in the same line with Donnelly (2016) he was found that, there were significant differences between pain intensity before and after videogames distraction, where total pain level means decreased following video game distraction technique. Also, Moosavi et al, (2019) supported this finding and found that there were significant reductions in pain for those wearing the head-mounted displays and also for those playing by the mobile device. Meanwhile, Hassannia et al, (2021) supported this finding in a similar study entitled and found that the virtual reality as a distraction technique significantly reduced pain at the onset of circumcision, during anesthesia and at the end of the circumcision.…”
Section: Effect Of Video Games On Postoperative Pain Among Preschool ...mentioning
confidence: 53%
“…Additionally, these findings were in line with Mokble (2007) who found that there was significant difference between the study and control group regarding decreasing body temperature, heart rates and respiratory rate after using distraction technique. Also, this finding was supported by Moosavi et al, (2019) in study about "The Effect of Medical Directed Play on the Severity of Pediatric Pain" and found that, there was significant difference between the average heart rate of the experimental group and the control group. Concerning pain intensity for the studied children, the current study presented that, there were highly statistically significant differences between pain intensity pre-, during and post-playing video games intervention These findings also agreed with Gates et al, (2020) he found that, important reduction in pain mean score in the group used digital technology such as video games or virtual reality than the control group.…”
Section: Effect Of Video Games On Postoperative Pain Among Preschool ...mentioning
confidence: 62%